Hypoalbuminemia and hypercalcemia are independently associated with poor treatment outcomes of anti-PD-1 immune checkpoint inhibitors in patients with recurrent or metastatic head and neck squamous cell carcinoma - Chiu, Tai-Jan; Huang, Tai-Lin; Chien, Chih-Yen; Huang, Wan-Ting; Li, Shau-Hsuan (World journal of surgical oncology, 2024)
Recent randomized phase III trials have demonstrated the efficacy of anti-programmed cell death 1 (PD-1) immune checkpoint inhibitors (ICIs) in treating patients with recurrent or metastatic head and neck squamous cell carcinoma (RMHNSCC). However, a large proportion of such patients still have poor response. This study aimed to identify biomarkers for predicting anti-PD-1 ICI treatment outcomes . We retrospectively analyzed 144 patients with RMHNSCC who received anti-PD-1 ICIs after progression to platinum-based chemotherapy between January 2017 and December 2022 at Kaohsiung Chang Gung Memorial Hospital. Data on clinicopathological parameters, albumin levels, calcium levels, and other pretreatment peripheral blood biomarkers, including total lymphocyte count, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), and prognostic nutritional index (PNI) were collected and correlated with the treatment outcome of anti-PD-1 ICIs. Low tumor proportion score (TPS), low combined positive score (CPS), NLR ≥ 5, PLR ≥ 300, hypercalcemia, hypoalbuminemia, and PNI < 45 were significantly correlated with poor response of ICIs. The overall response rates were 25% and 3% in patients with calcium < 10 mg/dL and calcium ≥ 10 mg/dL, respectively (P = 0.007). The overall response rates were 6% and 33% in patients with albumin < 4 g/dL and albumin ≥ 4 g/dL, respectively (P < 0.001). Univariate survival analysis showed that low TPS, low CPS, NLR ≥ 5,, hypercalcemia, hypoalbuminemia, and PNI < 45 were significantly associated with worse progression-free survival (PFS) and inferior overall survival (OS). Multivariate analysis revealed that calcium ≥ 10 mg/dL and albumin < 4 g/dL were independent poor prognosticators for worse PFS and inferior OS. The two-year OS rates were 26% and 9% in patients with calcium < 10 mg/dL and ≥ 10 mg/dL, respectively (P < 0.001). The two-year OS rates were 10% and 33% in patients with albumin < 4 g/dL and ≥ 4 g/dL, respectively (P < 0.001). Hypercalcemia and hypoalbuminemia can potentially predict poor treatment outcomes of anti-PD-1 ICIs in patients with RMHNSCC. Blood calcium and albumin levels may be helpful in individualizing treatment strategies for patients with RMHNSCC.